Effects of aerobic, strength, and combined training during pregnancy in the blood pressure: A systematic review and meta-analysis - Corso, Marcelo; Miarka, Bianca; Figueiredo, Tiago; Bragazzi, Nicola; Carvalho, Danilo; Dias, Ingrid (Frontiers in Physiology, 2022)
Gestational hypertension can lead to fetal complications, and, if untreated, high blood pressure during pregnancy may cause eclampsia and even death in the mother and fetus. Exercise is a strategy for preventing blood pressure disorders. There is little knowledge about the physiological impacts of different physical types of training on blood pressure during pregnancy. For that, this meta-analysis aimed to compare the effects of different physical exercise modalities (i.e., aerobic training - AT, strength training - ST, and combined training – AT+ST) on systolic blood pressure (SBP) and diastolic blood pressure (DBP) of pregnant women. A search was performed on PUBMED, LILACS, CINAHL, Sport discus, EMBASE, SCOPUS, and Cochrane Central Register of Controlled Trials to identify researchers. From 3,450 studies, 20 and 19 were included in the qualitative and quantitative analyses. AT studies presented a medium effect size (ES) on SBP [-0.29 (-2.95 to 2.36) p=.83], with substantial heterogeneity (I2=64%), and had a large impact on DBP [-1.34 (-2.98 to 0.30) p=.11], with moderate heterogeneity (I2=30%). ST researchers showed a large ES on SBP [-1.09 (-3.66 to 1.49) p=.41], with a reduced heterogeneity (I2=0%), and a medium ES on DBP [-0.26 (-2.77 to 2.19) p=.83] with moderate heterogeneity (I2=38%). AT + ST studies had a large ES on SBP [-1.69 (-3.88 to 0.49) p=.13] and DBP [-01.29(-2.26 to 0.31) p=.01] with considerable (I2=83%) and moderate heterogeneity (I2=47%), respectively. These findings are essential for developing new research protocols to avoid gestational hypertension and preeclampsia. AT+ST had a large impact on the SBP and DBP reduction; however, there is a need for more similar procedures to reduce heterogeneity between studies, promoting consensual results.